Pengendalian Mutu Pada Proses Produksi Di Tiga Usaha Kecil Menengah Tahu Kabupaten Bogor - Devi Sonalia; Musa Hubeis (IPB University, 2013)
Today the growth of Small and Medium Enterprises (SMEs) is increasing significantly along with the rise in competitiveness in this field. Accordingly entrepreneurs who want to get into the competition and do not want to be left behind by other SMEs in the business field have to pay attention to the quality of their product. The purpose of this study are: (1) to analyze the quality control (QC) on the production process in SMEs of Tofu (soybean cake) as Tahu Bambu, Tahu Bandung Ashor and Tahu Bandung; (2) to identify the factors which cause damage of Tofu as Tahu Bambu, Tahu Bandung Ashor and Tahu Bandung; (3) to identify the most influential factor affecting the quality of Tofu as Tahu Bambu, Tahu Bandung Ashor and Tahu Bandung; and (4) to assess the QC on the production process in the above three unit. The data used in this study were primary and secondary data. Primary data were obtained through direct observation and interviews with the SMEs, while the secondary data were taken from the internet and references such as books, journals and theses. Analysis tool used were Pareto Diagram, Cause and Effect Diagram and Control Chart. It is from Cause-Effect diagram that the factors affecting damage in three SMEs of Tahu were revealed, i.e human, raw materials, machines and tools, methods and environment with the main cause of most influence through analysis Pareto diagram is one piece. Quality control of the SMEs Tahu Bambu and SMEs Tahu Bandung analyzed using by p Control Charts indicated that they were controlled.Keywords: Quality controls, Cause and effect diagram, Pareto chart, Control chart